Dokumen Kontrak : maintenance works on low voltage electrical services in Universiti Teknologi Malaysia Skudai Johor (package A) - Universiti Teknologi Malaysia. Pejabat Harta Bina; Universiti Teknologi Malaysia; PTIS Engineering Sdn. Bhd (2010)
PRZSL